2013
DOI: 10.3233/thc-130751
|View full text |Cite
|
Sign up to set email alerts
|

Development of model for assessing the acceptance level of users in rural healthcare system of Tamilnadu, India

Abstract: BACKGROUND: HMIS will incorporate a paradigm shift in health such as removing manual records and transformation of data through the complex structure of health departments in Tamilnadu. Thus developing a model of technology acceptance in HMIS contest is important and necessary in order to promote usage of the HMIS in rural health care system. OBJECTIVE: The papers purpose is to formulate a model of technology acceptance of Health Management Information System (HMIS) by generating and validating a research mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…TAM-3 expanded on earlier versions of the model by incorporating social norms, human and social change processes, and adding additional determinants of perceived ease of use and perceived usefulness [ 28 , 31 ]. In India, the TAM model has been used and adapted to determine the factors of acceptance of health information technology by outpatients in a private-sector hospital [ 33 ]; to assess adoption of health information technology by rural healthcare workers [ 34 ]; and to model acceptance and usage of a health management information system among workers in a rural healthcare system [ 35 ], but it has not been applied to any technologies designed to improve quality of care.…”
Section: Methodsmentioning
confidence: 99%
“…TAM-3 expanded on earlier versions of the model by incorporating social norms, human and social change processes, and adding additional determinants of perceived ease of use and perceived usefulness [ 28 , 31 ]. In India, the TAM model has been used and adapted to determine the factors of acceptance of health information technology by outpatients in a private-sector hospital [ 33 ]; to assess adoption of health information technology by rural healthcare workers [ 34 ]; and to model acceptance and usage of a health management information system among workers in a rural healthcare system [ 35 ], but it has not been applied to any technologies designed to improve quality of care.…”
Section: Methodsmentioning
confidence: 99%
“…46,47 Another study comparing the TAM and the UTAUT among physicians concluded that the usage intentions were strongly associated with the performance expectancy on attitude and attitude concepts. 48 Manimaran and Lakshmi 49 formulated an integrated TAM for Health Management Information System and concluded that health workers' innovativeness and voluntariness had a direct and positive influence on these intentions. Similarly, Smith and Motley 50 found that e-prescribing acceptance was predicted by the technological sophistication, operational factors, and maturity factors constructs, i.e., ease-of-use variables derived from the TAM.…”
Section: Comparison Of Other Technology Acceptance Models With Tammentioning
confidence: 99%
“…A study in India reported that change management and capacity building issues were key factors affecting the performance of key national and state‐level HIS . Studies found that HMIS usage and increased acceptance of HMIS among health workers was important for uptake of HMIS and that individual motivation and skills affected data quality . However, one study reported that data quality issues were compounded by information work flow barriers and unfriendly software features that adversely affected data flow and required institutional capacity building in addition to individual trainings .…”
Section: Resultsmentioning
confidence: 99%